Determinação de As, Cd, Pb e Zn por voltametria no médio curso do Rio Paraíba do Sul - Itatiaia - RJ. - Costa, Julie Barnes de Souza (2009)
The trace elements, As Cd Pb and Zn occur in nature in a variety of chemical forms, including organic and inorganic species. They come from natural sources and anthropogenic activities. Because of the risk of chronic poisoning of these elements, the maximum values allowed for them in water have decreased over years according to the World Health Organization and CONAMA Resolution 357/2005. Currently, the maximum permissible concentrations for dinking water are 10 μg.L-1, 1 μg.L-1, 10 μg.L-1 e 180 μg.L-1 for As, Cd, Pb and Zn respectively (resolution 357/CONOMA 2005). This study aimed to develop and validate an analytical method using the Stripping Voltammetry for determining the concentrations of As, Cd, Pb and Zn in water samples from the middle course of Paraíba do Sul river, at the Hydroelectric of Funil Itatiaia RJ, and check the influence of the dam s reservoir on water concentrations of these elements. The developed voltammetric method showed adequate sensitivity and selectivity, with low limits of detection: 0,002 μg.L-1 for As, 0,002 μg.L-1 for Cd, 0,006 μg.L-1 for Pb and 0,095 μg.L-1 for Zn. The results demonstrate the possible influence of the dam, acting as a geochemical barrier, accumulating As, Cd and Pb. When compared to the maximum allowed by CONAMA this study found concentrations significantly lower for As, Pb and Zn and higher for Cd.